2005
DOI: 10.1111/j.1467-9353.2004.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Effects on Consumers' Willingness to Purchase Irradiated Food Products

Abstract: This study assessed the effect of information related to the food irradiation process on consumers' willingness to purchase irradiated food products and the perceived consumer segment to which they belonged ("strong buyer," "interested," "doubter," or "rejector" of irradiated food). Two types of information were presented: the nature and benefits of food irradiation and information about two ways in which food can be irradiated. Positive shifts in the responses were observed in both the consumer segment to whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 2 publications
2
27
0
1
Order By: Relevance
“…This observation is in agreement with findings of some researchers [24,25] who carried out analysis to assess consumer attitudes to irradiated foods. Niemira and Fan [26], observed that treatment up to 0.5 kGy did not change the texture of different types of iceberg lettuce.…”
Section: Resultssupporting
confidence: 82%
“…This observation is in agreement with findings of some researchers [24,25] who carried out analysis to assess consumer attitudes to irradiated foods. Niemira and Fan [26], observed that treatment up to 0.5 kGy did not change the texture of different types of iceberg lettuce.…”
Section: Resultssupporting
confidence: 82%
“…Other studies (e.g., Boccaletti & Moro, 2000;Cox, Evans, & Lease, 2007;Cox, Evans, & Lease, 2008;Frezen, Majchrowicz, Buzby, & Imhoff, 2000;Hallman & Aquino, 2003;Levy, 2001;McClusky, Ouchi, Grimsrud, & Wahl, 2001;Nayga, Aiew, & Nichols, 2005;Rodriguez, 2007) have used survey approaches to study the relation between attitudes toward, and self-rated knowledge of, food technologies. In general, these studies find a positive relation between knowledge and attitudes toward a given food technology; although some find a negative relation (e.g., Boccaletti & Moro, 2000) or no relation (Cox et al, 2007(Cox et al, , 2008 between knowledge, information and acceptance of foods derived from new technologies.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The choice between probit and logit should be based on goodness of fit. These CDFs are frequently used to analyze dichotomous (0-1) binary data and in the context of consumer purchasing evaluation, where the consumer is making a choice between two food products or buying and not buying (Johnston, Wessells, Donath, & Asche, 2001;Nayga, Aiew, & Nichols, 2005), but they are also suitable for examining purchase intent on a scale or as a proportion.…”
Section: Methods Of Analysismentioning
confidence: 99%